2019
DOI: 10.1155/2019/3212594
|View full text |Cite
|
Sign up to set email alerts
|

A Further Analysis on Ti6Al4V Lattice Structures Manufactured by Selective Laser Melting

Abstract: Mechanical and architectural features play an important role in designing biomedical devices. The use of materials (i.e., Ti6Al4V) with Young's modulus higher than those of natural tissues generally cause stress shielding effects, bone atrophy, and implant loosening. However, porous devices may be designed to reduce the implant stiffness and, consequently, to improve its stability by promoting tissue ingrowth. If porosity increases, mass transport properties, which are crucial for cell behavior and tissue ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Current efforts to reduce the stiffness of metallic lattice structures for biomedical implants are directed toward changing the material, the unit cell type, the porosity, [ 40 ] and the pore interconnectivity [ 45 ] to ensure osseointegration and to reduce the possibility of implant loosening. To improve tissue integration, biomedical implants have previously been coated with hydrogels [ 46 ] to provide better adhesion to surrounding tissues [ 47 ] and antibacterial protection.…”
Section: Resultsmentioning
confidence: 99%
“…Current efforts to reduce the stiffness of metallic lattice structures for biomedical implants are directed toward changing the material, the unit cell type, the porosity, [ 40 ] and the pore interconnectivity [ 45 ] to ensure osseointegration and to reduce the possibility of implant loosening. To improve tissue integration, biomedical implants have previously been coated with hydrogels [ 46 ] to provide better adhesion to surrounding tissues [ 47 ] and antibacterial protection.…”
Section: Resultsmentioning
confidence: 99%
“…The justification for selecting these three biomaterials was based on their availability, reported biocompatibility, prospect of CAD/CAM manufacturing, and mechanical properties, which are either higher than or are comparable to that of cortical bone (Table 6) [35][36][37]. It must however be noted that the choice of material should be based mainly on the elastic modulus of the biomaterial in comparison to that of natural bone [17][18][19]. Maietta et al reported that it is possible to modify the elastic properties of titanium implants manufactured using an additive process, without affecting their mechanical performance, by incorporating advanced porous and lattice structures [17].…”
Section: Discussionmentioning
confidence: 99%
“…It must however be noted that the choice of material should be based mainly on the elastic modulus of the biomaterial in comparison to that of natural bone [17][18][19]. Maietta et al reported that it is possible to modify the elastic properties of titanium implants manufactured using an additive process, without affecting their mechanical performance, by incorporating advanced porous and lattice structures [17]. In addition to fabrication of implants with Young's modulus closer to that of natural bone, porous structures also help minimize stress shielding effect [17].…”
Section: Discussionmentioning
confidence: 99%
“…The PBS should be designed in a way to enable the required magnitude of deformations in the specific directions under the most common load/constraint cases inherent to the patient [ 2 , 4 ]. Actually, properly designed construction and material selection for PBS can provide a suitable strength of the structure that will enable the required magnitude of deformation and fatigue resistance ( Figure 4 ).…”
Section: Objectives and Challenges Of Pbs Applicationmentioning
confidence: 99%
“…At the same time, it should endure the necessary number of cycles of the load that will be imposed while the recovery process ongoing without losing its support function. There are a few research endeavours reporting on the optimization of lattice-like scaffold structure in terms of mechanical characteristics required for the specific patient [ 2 , 4 ].…”
Section: Objectives and Challenges Of Pbs Applicationmentioning
confidence: 99%